Air Traffic Management and Systems II Selected Papers of the 4th ENRI International Workshop, 2015 - Electronic Navigation Research Institute; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book is a compilation of selected papers from the 4th ENRI International Workshop on ATM/CNS (EIWAC2015). The work focuses on novel techniques for aviation infrastructure in air traffic management (ATM) and communications, navigation, surveillance, and informatics (CNSI) domains. The contents make valuable contributions to academic researchers, engineers in the industry, and regulators of aviation authorities. As well, readers will encounter new ideas for realizing a more efficient and safer aviation system. .
Introduction to the fourth ENRI International Workshop on ATM/CNS (EIWAC 2015) -- Large Scale 4D Trajectory Planning -- Aircraft Trajectory Planning by Artificial Evolution and Convex Hull Generations -- Homotopy Route Generation Model for Robust Trajectory Planning -- Numerical Investigation on Flight Trajectory Optimization Methods -- Optimization-Based Performance Assessment on 4D-Trajectory Based Operations with Track Data -- Future Arrival Management Collaborating with Trajectory-Based Operations -- Quantitative Analysis of Conflict between Aircraft by Using Radar Track Data -- Optimizing the Design of a Route in Terminal Maneuvering Area Using Branch and Bound -- Arrival Time Assignment by Dynamic Programming Optimization -- A Dynamic Multi-Commodity Flow Optimization Algorithm for Estimating Airport Network Capacity -- Downlink Aircraft Parameters based High-accuracy Tracking System for Air Traffic Surveillance -- Experimental study of Photonic based Radar for FOD detection systems using 90GHz-band.
Keywords: Telecommunication; Aerospace engineering; Astronautics; Mathematical models; Mathematical optimization; Computational intelligence; Communications Engineering, Networks; Aerospace Technology and Astronautics; Mathematical Modeling and Industrial Mathematics; Optimization; Computational Intelligence